In vitro Maturation (IVM) of human oocytes - Strowitzki, Thomas (Archives of gynecology and obstetrics, 2013)
In vitro maturation is a technique of assisted reproduction which in contrast to standard IVF or ICSI almost fully avoids hormonal stimulation. Immature oocytes will be fully matured in vitro within 24 h after oocyte collection. The method was introduced in the early nineties and is indicated in patients at high risk for ovarian hyperstimulation. Results are almost comparable to standard techniques. Up to now no elevated risk for fetal malformations has been described. IVM is a suitable alternative in IVF for an exactly defined subgroup of patients, in particular patients with PCOS, but still does not replace standard techniques.